2019
DOI: 10.3390/ani9050228
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Rodent Pathogens in Wild Rats from the Island of St. Kitts, West Indies

Abstract: A pilot seroprevalence study was conducted to document exposure to selected pathogens in wild rats inhabiting the Caribbean island of St. Kitts. Serum samples collected from 22 captured wild rats (Rattus norvegicus and Rattus rattus) were tested for the presence of antibodies to various rodent pathogens using a rat MFI2 serology panel. The samples were positive for cilia-associated respiratory bacillus (13/22; 59.1%), Clostridium piliforme (4/22; 18.2%), Mycoplasma pulmonis (4/22; 18.2%), Pneumocystis carinii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
1
10
0
4
Order By: Relevance
“…Previous studies identified RVA in other species of rodents and shrews using RT-PCR in Germany (Sachsenröder et al 2014 ), China (Li et al 2016 ), Brazil (Tonietti et al 2013 ), and New York (Williams et al 2018 ). In contrast, studies in Australia (McInnes et al 2011 ), West Indies (Boey et al 2019 ), and Western Europe (Mähler and Köhl 2009 ) reported rotavirus antibodies in rodents. However, published literature on RVA in small mammals is scarce worldwide.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies identified RVA in other species of rodents and shrews using RT-PCR in Germany (Sachsenröder et al 2014 ), China (Li et al 2016 ), Brazil (Tonietti et al 2013 ), and New York (Williams et al 2018 ). In contrast, studies in Australia (McInnes et al 2011 ), West Indies (Boey et al 2019 ), and Western Europe (Mähler and Köhl 2009 ) reported rotavirus antibodies in rodents. However, published literature on RVA in small mammals is scarce worldwide.…”
Section: Discussionmentioning
confidence: 94%
“…A study from St. Kitts analysed the nearly whole genomes of rotavirus-A strains from pigs and African green monkeys, providing evidence for porcine to simian interspecies transmission events . In another study from St. Kitts, antibodies against Rotavirus-B strain IDIR were detected in a serum sample from a free roaming rat (Boey et al, 2019).…”
Section: Reoviridaementioning
confidence: 94%
“…Antibodies against parvoviruses have also been reported in diarrhoeic (37.5%, n = 32) and non-diarrhoeic cattle (25.9%, n = 27) on Trinidad (Adesiyun et al, 2001), and in free roaming rodents (Kilham rat virus, rat parvovirus and rat minute virus) on St. Kitts (Boey et al, 2019).…”
Section: Parvoviridaementioning
confidence: 98%
See 1 more Smart Citation
“…The parvoviruses also cause clinically silent in rodents and, sometimes, persistent infections that are associated with prolonged virus release [7]. Given the increasing threats of parvovirus infection to laboratory and wild rodents [8][9][10], it is of great importance to comprehend the distribution and host range of the parvoviruses in nature.…”
Section: Introductionmentioning
confidence: 99%